On Dynamic Properties of Two Models of Beam on Nonlinear Foundation Subjected to Moving Load - Grzyb, A. (Engineering Transactions, 1993)
The subjects of consideration are the infinite Bernoulli - Euler and Timoshenko models of a beam resting on a nonlinear visco-elastic foundation. The beams are subjected to a distributed inertialess loading constant in a given sector and moving with a constant velocity. Nonlinearity of the foundation was assumed in the form of a piece-wise linear characteristic of elasticity. Results obtained for the Bernoulli - Euler beam have been compared to the corresponding results obtained for a Timoshenko beam. The considered problems may find same applications in modern transportation systems.